Upaya Meningkatkan Motivasi Belajar Dan Literasi Anak Melalui Kelas Literasi Online Di Selingkar - Sri Utami; Nurul Azizah (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Batch 1 Literacy Class is a program that aims to increase children's learning motivation and literacy through the use of online literacy platforms. In this program, various methods and strategies are used to create a fun, interactive learning environment and motivate children to be more actively involved in literacy activities. The method of implementing this program involves interactive stories, discussions, practical activities, and presentations of the participants' work. Each program session is focused on a different topic, such as organic farming, the role of farmers, the impact of climate change, and the challenges faced by farmers in dealing with locusts that attack crops.agriculture and climate change. Through stories and true stories, participants are invited to understand the importance of literacy in the context of agriculture and the environment. The results of this program show an increase in learning motivation and understanding of children's literacy. Participants showed high involvement in online literacy classes and were able to apply their knowledge and creativity in finding solutions to problems encountered in agriculture. In addition, the output of the study worksheet program and positive feedback from participants and parents are indicators of the program's success in increasing children's learning motivation and literacy. This program provides significant benefits for children's literacy development, increases their motivation to learn, and helps them develop essential literacy skills.